Generation of novel n-p-n (CeO2-PPy-ZnO) heterojunction for photocatalytic degradation of micro-organic pollutants - Rajendran, S.; Hoang, T.K.A.; Trudeau, M.L.; Jalil, A.A.; Naushad, M.; Awual, Rabiul (ELSEVIER SCI LTD, 2022)
Recently, hetero junction materials (p-n-p and n-p-n) have been developed for uplifting the visible light activity to destroy the harmful pollutants in wastewater. This manuscript presents a vivid description of novel n-p-n junction materials namely CeO2-PPy-ZnO. This novel n-p-n junction was applied as the photocatalyst in drifting the mobility of charge carriers and hence obtaining the better photocatalytic activity when compared with p-n and pure system. Such catalyst's syntheses were successful via the copolymerization method. The structural, morphological and optical characterization techniques were applied to identify the physio-chemical properties of the prepared materials. Additionally, the superior performance of this n-p-n nanostructured material was demonstrated in the destruction of micro organic (chlorophenol) toxic wastes under visible light. The accomplished ability of the prepared catalysts (up to 92% degradation of chlorophenol after 180 min of irradiation) and their profound degradation mechanism was explained in detail.